Die verhouding tussen kerk en staat: Enkele modelle met verwysing na die reg van opstand teen die staat - Smith, D. J. (Hervormde teologiese studies, 1988)
The interrelationship between church and state: Some theological models with reference to the right to revolt against the state In this paper consideration is given to the theological models concerning the relation church and state, as accepted by the Roman Catholic Church, Luther, Calvin, Karl Barth and the theologies with a revolutionary inclination like the Political Theology, Theology of Liberation, Revolutionary Theology and the Kairos Document. The right to revolt against the state, as perceived within each model, is also dealt with.